EFFICACY AND ADVERSE EFFECTS OF ANTI EPILEPTIC DRUGS. Issue 12 (15th November 2016) - Wieshmann, Udo; Baker, Gus
Abstract : Objective: To ascertain effectiveness and adverse effects of anti epileptic drugs (AED) using the UKAED register (www.ukaed.info). Methods: Patients on Carbamazepine (CBZ) n=91, Valproate (VPA) n=61, Lamotrigine (LTG) n=105, Levetiracetam (LEV) n=72, and healthy control subjects on no medication (CTR) n=51 anonymously provided information on seizure frequency and completed the Liverpool Adverse Event Profile (LAEP). Results: Seizure free rates were similar (CBZ/VPA/LTG/LEV=0.49/0.61/0.54/0.47). Mean LAEPscores were significantly higher in patients than in control subjects (CBZ/VPA/LTG/LEV/CTRL=41.27/42.21/39.66/39.86/43.07/29.69). Tiredness (77%), memory problems (62%), sleepiness (54%), difficulty concentrating (51%), nervousness (50%), restlessness (45%), dizziness (43%), unsteadiness (40%), depression (40%), feeling of anger (37%), shaky hands (34%) were all significantly more frequent in patients than in control subjects. Furthermore, anger and unsteadiness were significantly more frequent in LEV (54%, 51%), shaky hands were significantly more frequent in VPA (46%) and depression was significantly more frequent in CBZ (54%) than in the other three AED. Patients with depression and active epilepsy had significantly higher meanLAEP scores. Conclusion: The efficacy was similar, adverse effects were extremely common. Signifcant associations were found for anger and unsteadiness and LEV, for shaky hands and VPA and depression and CBZ.